2019
DOI: 10.2967/jnumed.118.225235
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Absorbed Doses and Correlations with Hematologic Response During 177Lu-DOTATATE Treatments Are Influenced by Image-Based Dosimetry Method and Presence of Skeletal Metastases

Abstract: This study aimed to compare different image-based methods for bone marrow dosimetry and study the dose–response relationship during treatment with 177Lu-DOTATATE in patients with and without skeletal metastases. Methods: This study included 46 patients with advanced neuroendocrine tumors treated with at least 2 fractions of 177Lu-DOTATATE at Sahlgrenska University Hospital. High- and low-uptake compartments were automatically outlined in planar images collected at 2, 24, 48, and 168 h after injection. The bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
60
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 32 publications
6
60
0
7
Order By: Relevance
“…Nevertheless, a recent prospective dosimetry study demonstrated that an increased number of treatments can be given based on total absorbed kidney dose (3), thereby avoiding undertreatment. In addition, doseresponse relationships have been reported for the dose-limiting organs kidneys and bone marrow, indicating the potential for dosimetry as one important factor in the individualized treatment protocol (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a recent prospective dosimetry study demonstrated that an increased number of treatments can be given based on total absorbed kidney dose (3), thereby avoiding undertreatment. In addition, doseresponse relationships have been reported for the dose-limiting organs kidneys and bone marrow, indicating the potential for dosimetry as one important factor in the individualized treatment protocol (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the theragnostic nature of the 177 Lu-DOTA-TATE molecule, SPECT images can also be made alongside its therapeutic action to verify in vivo dosimetry and biodistribution. Two studies used this principle and found the estimated dose to the bone marrow to be much higher than blood-based dosimetry methods [36,37]. One of them also showed correlations between bone marrow dose, and reduction in platelet counts [37].…”
Section: Bone Marrowmentioning
confidence: 99%
“…Two studies used this principle and found the estimated dose to the bone marrow to be much higher than blood-based dosimetry methods [36,37]. One of them also showed correlations between bone marrow dose, and reduction in platelet counts [37]. RNTs are usually delivered over multiple cycles, and these post-therapy scans can be used to plan subsequent therapy cycles and even assess potential toxicity between them.…”
Section: Bone Marrowmentioning
confidence: 99%
“…A reason for this finding might be the high variability of bone marrow dose depending on the method used. SPECT-based activity concentration fluctuated 100% (L5 median 24.2 kBq/ml, T11 median 47.8 kBq/ml) depending on the vertebral body examined [7]. Consequently, bone marrow doses varied depending on the used method: planar scintigraphy 0.19 Gy/7.4 GBq, SPECT of L4 0.36 Gy/ 7.4 GBq, SPECT of all visible vertebra 0,40 Gy/7.4 GBq, SPECT of all lumbar vertebra 0.39 Gy/7.4 GBq, and SPECT of all thoracic vertebra 0.46 Gy/7.4 GBq.…”
Section: In Not Gamma-emitting Radionuclides Such As [ 90 Y]mentioning
confidence: 99%